Virginia Woolf and Christian culture - De Gay, Jane, 1966- (Edinburgh University Press, 2017)
This wide-ranging study demonstrates that Woolf, despite her agnostic upbringing, was profoundly interested in, and knowledgeable about, Christianity as a faith and a socio-political movement.